STRATEGI PEMBELAJARAN AKIDAH AKHLAK DALAM MENINGKATKAN HASIL BELAJAR PADA ASPEK AFEKTIF SELAMA COVID-19 DI MTs BPP BAWAN - Nurnajmi, Nurnajmi; Lahmi, Ahmad; Halim, Syaflin (SOKO GURU: Jurnal Ilmu Pendidikan, 2022)
Learning outcomes in the affective aspect are one of the three realms of ability that must be possessed by students after following the learning process. To achieve abilities in this aspect, strategies are needed that are in accordance with the conditions, objectives and learning materials. Therefore, this study aims to find strategies that can be used in improving Akidah Akhlak learning outcomes in affective aspects during covid-19 at MTs BPP Bawan. The research was conducted with a quality approach of ethnographic type, which is an approach used to understand the culture and behavior of informants based on learning culture during covid-19. The results of the study were the implementation of online learning for moral teachers at MTs S BPP Bawan in improving affective aspect learning outcomes carried out through several strategies starting from making designs for the implementation of online learning, preparing learning media, determining scenarios, preparing interesting materials, determining methods and determining approaches. Its application is carried out through habituation and developing the values of honesty. The disadvantage of learning strategies in improving affective aspect learning outcomes during this pandemic is that it is felt less than optimally, and it does not create good interactions between teachers and students. Meanwhile, the advantage is the acceleration of mastery of technology, it is more flexible and can be repeated.